2016
DOI: 10.1371/journal.pone.0152873
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inlet Blood Flow Velocity Predicts Low Wall Shear Stress in the Cephalic Arch of Patients with Brachiocephalic Fistula Access

Abstract: BackgroundAn autogenous arteriovenous fistula is the optimal vascular access for hemodialysis. In the case of brachiocephalic fistula, cephalic arch stenosis commonly develops leading to access failure. We have hypothesized that a contribution to fistula failure is low wall shear stress resulting from post-fistula creation hemodynamic changes that occur in the cephalic arch.MethodsTwenty-two subjects with advanced renal failure had brachiocephalic fistulae placed. The following procedures were performed at map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 32 publications
5
30
0
Order By: Relevance
“…In a parallel study, we have statistically and computationally identified a physiologic range of WSS in the cephalic vein pre-surgery. This range was determined to be 0.076 ≤ τ w ≤ 0.76 Pa [61] , which is consistent with the range given in previous literature [22] .…”
Section: A Shape Optimization Model Of Neointimal Hyperplasiasupporting
confidence: 87%
See 3 more Smart Citations
“…In a parallel study, we have statistically and computationally identified a physiologic range of WSS in the cephalic vein pre-surgery. This range was determined to be 0.076 ≤ τ w ≤ 0.76 Pa [61] , which is consistent with the range given in previous literature [22] .…”
Section: A Shape Optimization Model Of Neointimal Hyperplasiasupporting
confidence: 87%
“…The flow is assumed to be Newtonian. Pulsatility and non-Newtonian effects were both attended to previously and were found to be insignificant in our patient cohort [61,62,63,64,77,75,76] . WBV for the CFD simulation is taken to be the patient-specific high-shear rate asymptotic viscosity values from the viscometry tests [62,78] .…”
Section: A Shape Optimization Model Of Neointimal Hyperplasiasupporting
confidence: 59%
See 2 more Smart Citations
“…25 More recent work, undertaken specifically in the context of vascular fluid mechanics, includes studies of stenotic flows, 26 pulsatile flow in curved pipes, [27][28][29][30] flow in helical pipes, [31][32][33][34] and flow at junctions. [35][36][37] In terms of simulating flow in AVF configurations, there have been a range of previous Computational Fluid Dynamics (CFD) studies, including 1D simulations, [38][39][40] 2D simulations, 41 3D simulations with rigid walls in idealised geometries, [42][43][44][45][46][47] 3D simulations with rigid walls in more realistic geometries, [48][49][50][51][52][53][54][55] and simulations with distensible walls. 56 Of these studies, several investigated flow unsteadiness.…”
Section: Introductionmentioning
confidence: 99%